Discovery and Characterization of Novel Anti-schistosomal Properties of the Anti-anginal Drug, Perhexiline and Its Impact on Schistosoma mansoni Male and Female Reproductive Systems. - Alessandra Guidi; Cristiana Lalli; Emerald Perlas; Giulia Bolasco; Martina Nibbio; Edith Monteagudo; Alberto Bresciani; Giovina Ruberti (Public Library of Science (PLoS), 2016)
Schistosomiasis, one of the world's greatest human neglected tropical diseases, is caused by parasitic trematodes of the genus Schistosoma. A unique feature of schistosome biology is that the induction of sexual maturation as well as the maintenance of the differentiation status of female reproductive organs and egg production, necessary for both disease transmission and pathogenesis, are strictly dependent on the male. The treatment and most control initiatives of schistosomiasis rely today on the long-term application of a single drug, praziquantel (PZQ), mostly by campaigns of mass drug administration. PZQ, while very active on adult parasites, has much lower activity against juvenile worms. Monotherapy also favors the selection of drug resistance and, therefore, new drugs are urgently needed.Following the screening of a small compound library with an ATP-based luminescent assay on Schistosoma mansoni schistosomula, we here report the identification and characterization of novel antischistosomal properties of the anti-anginal drug perhexiline maleate (PHX). By phenotypic worm survival assays and confocal microscopy studies we show that PHX, in vitro, has a marked lethal effect on all S. mansoni parasite life stages (newly transformed schistosomula, juvenile and adult worms) of the definitive host. We further demonstrate that sub-lethal doses of PHX significantly impair egg production and lipid depletion within the vitellarium of adult female worms. Moreover, we highlighted tegumental damage in adult male worms and remarkable reproductive system alterations in both female and male adult parasites. The in vivo study in S. mansoni-patent mice showed a notable variability of worm burdens in the individual experiments, with an overall minimal schistosomicidal effect upon PHX treatment. The short PHX half-life in mice, together with its very high rodent plasma proteins binding could be the cause of the modest efficacy of PHX in the schistosomiasis murine model.Overall, our data indicate that PHX could represent a promising starting point for novel schistosomicidal drug discovery programmes.